First Evidence of Fowl Adenovirus Induced Inclusion Body Hepatitis in Chicken in Bangladesh. (3rd January 2023) - Islam, Mohammad Nazrul; Rahman, Md. Mostafizer; Rahman, Md. Khalesur; Alam, Jahangir
Abstract : Background . The livestock sector contributes 1.90% to the GDP in Bangladesh during 2021–22. Poultry is one of the important subsectors struggling with diseases. Fowl adenoviruses (FAdVs) cause numerous diseases resulting in economic losses to the poultry industry worldwide. Several FAdV serotypes cause inclusion body hepatitis in chicken. Although FAdV infection was suspected, there was no confirmatory report from Bangladesh. The study was conducted to investigate the FAdV infection and antibodies in chicken. Methods. A total of 50 samples, each composed of liver and spleen, were collected from different chickens of Gazipur, Dinajpur, and Panchagarh district. Each location belongs to A, B, and C poultry zones of Bangladesh, respectively. Viruses were detected by real-time PCR and conventional PCR. Blood samples ( n = 303) were collected at the beginning and after the recovery from infection and tested by indirect ELISA. Sequencing of PCR products was done for serotyping and phylogenetic analysis. Results. Clinical signs were observed including anorexia, drowsiness, ruffled feathers, reduced body weight, lack of uniformity, and high mortality (15–25%). Enlarged friable liver with yellow to tan color mottled with the focal soft area, fluid in pericardial sac, swollen and hemorrhagic kidneys, enlarged congested spleen and pancreas, etc. were found on postmortem examination. FAdVs were detected in 90% of the flocks except commercial layer flock from Dinajpur. Three serotypes, namely, 8b (70%), 11 (10%), and 5 (10%) were detected. Anti-FAdV antibody was detected in 80% flocks at the beginning of infection and in 90% of the flocks after recovery from infection. The antibody titer increases significantly (p < 0.05 ) after recovery from infection. Phylogenetic analysis revealed that the Bangladeshi FAdVs have close identity with viruses from Asia, Europe, and South and North America. Conclusions. These findings suggested that several introductions of FAdVs were taken place in Bangladesh. To combat the disease, vaccination along with maintenance of biosecurity is essential.